Research Update: Behind the High Efficiency of Hybrid Perovskite Solar Cells - Fakharuddin, Azhar; De Rossi, Francesca; Watson, Trysten M.; Scmidt-Mende, Lukas; Rajan, Jose (American Institute of Physics, 2016)
Perovskite solar cells (PSCs) marked tremendous progress in a short period of time and offer bright hopes for cheap solar electricity. Despite high power conversion efficiency >20%, its poor operational stability as well as involvement of toxic, volatile, and less-abundant materials hinders its practical deployment. The fact that degradation and toxicity are typically observed in the most successful perovskite involving organic cation and toxic lead, i.e., CH3NH3PbX3, requires a deep understanding of their role in photovoltaic performance in order to envisage if a non-toxic, stable yet highly efficient device is feasible. Towards this, we first provide an overview of the basic chemistry and physics of halide perovskites and its correlation with its extraordinary properties such as crystal structure, bandgap, ferroelectricity, and electronic transport. We then discuss device related aspects such as the various device designs in PSCs and role of interfaces in origin of PV parameters particularly open circuit voltage, various film processing methods and their effect on morphology and characteristics of perovskite films, and the origin and elimination of hysteresis and operational stability in these devices. We then identify future perspectives for stable and efficient PSCs for practical deployment.